2003
DOI: 10.1039/b307177b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of quinoxalines, dihydropyrazines, pyrazines and piperazines using tandem oxidation processes

Abstract: Alpha-hydroxyketones undergo MnO2-mediated oxidation followed by in situ trapping with aromatic or aliphatic 1,2-diamines to give quinoxalines or dihydropyrazines, respectively, in a one pot procedure which avoids the need to isolate the highly reactive 1,2-dicarbonyl intermediates. Modifications of the procedure allow the formation of pyrazines and piperazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(44 citation statements)
references
References 19 publications
0
43
0
1
Order By: Relevance
“…1 Although rarely described in nature, synthetic quinoxaline ring is a part of a number of antibiotics which are known to inhibit the growth of Grampositive bacteria and are also active against various transplantable tumors. 2 From the synthesis standpoint, despite remarkable efforts in the last decade, [3][4][5][6][7] the development of effective methods for the synthesis of quinoxaline is still an important challenge. By far, the most common method relies on the condensation of an aryl 1,2-diamine with a 1,2-dicarbonyl compound in refluxing ethanol or acetic acid for 2-12 h. For example, the condensation of 1,2-diaminobenzene with benzil provides quinoxaline 1a in literature yields ranging from 34-85% depending on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although rarely described in nature, synthetic quinoxaline ring is a part of a number of antibiotics which are known to inhibit the growth of Grampositive bacteria and are also active against various transplantable tumors. 2 From the synthesis standpoint, despite remarkable efforts in the last decade, [3][4][5][6][7] the development of effective methods for the synthesis of quinoxaline is still an important challenge. By far, the most common method relies on the condensation of an aryl 1,2-diamine with a 1,2-dicarbonyl compound in refluxing ethanol or acetic acid for 2-12 h. For example, the condensation of 1,2-diaminobenzene with benzil provides quinoxaline 1a in literature yields ranging from 34-85% depending on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…5H 2 0 [28], Zn/L-Proline [29] and CAN [30] have been explored. Oxidative couplings of epoxides and ene-1,2-diamines [31] catalyzed by Bi(0), Pd(OAc) 2 , RuCl 2 -(PPh 3 ) 3 -TEMPO, and MnO 2 have been reported [32][33][34]. The condensation has also been accomplished under catalyst-free conditions, but needs microwave heating [35].…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxalines play an important role as a basic skeleton for the design of a number of antibiotics such as echinomycin, actinomycin, and leromycin. It has been reported that these compounds inhibit the growth of gram-positive bacteria, and are active against various transplantable tumors [1,2] The quinoxaline ring is also a constituent of many pharmacologically and biologically active compounds such as insecticides, fungicides, herbicides, and anthelminitics [3,4]. Quinoxaline derivatives have found application in dyes [5], electron luminescent materials [6], organic semiconductors [7], chemically controllable switches [8], as building blocks for the synthesis of anion receptors [9], cavitands [10], dehydroannulenes [11], DNA cleaving agents [12] and also serve as useful rigid subunits in macrocyclic receptors or in molecular recognition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Improved methods have been reported using the different catalysts including I 2 (Bhosale et al 2005, More et al 2005, SA (Darabi et al 2007), Montmorillonite K-10 (Huang et al 2008), polyaniline-sulfate salt (Srinivas et al 2007), H 6 P 2 W 18 O 62 . 24H 2 O , InCl 3 (Hazarika et al 2007), MnCl 2 (Heravi et al 2008), CuSO 4 .5H 2 O , Zn[(L)proline] , CAN (More et al 2006), Ga(OTf) 3 (Cai et al 2008), PEG-400 (Zhang et al 2010), Pd(OAc) 2 , MnO 2 (Raw et al 2003), keggin heteropoly acid (Huang et al 2009), and IBX (Heravi et al 2006) have been explored. In continuation of our studies (Mohammadi et al 2008(Mohammadi et al , 2009), on the application of nanoporous heterogeneous solid catalyst to organic synthesis, in this paper we want to report an efficient method for the preparation of quinoxaline derivatives using SBA-Pr-SO 3 H as a nanoporous heterogeneous acid catalyst.…”
Section: Introductionmentioning
confidence: 99%